The role of recreational flow experience and well-being on re-participation intention: recreational sport participants - Alican Bayram; Ilimdar Yalcin; Enis Sahin; Nurullah Emir Ekinci; Laurentiu-Gabriel Talaghir; Teodora-Mihaela Iconomescu (Frontiers in Psychology)
IntroductionRecreational sports activities can offer participants many physical, psychological, and social benefits. The flow state they feel during participation can give them a sense of satisfaction and positively change their attitudes toward participation in recreational sports activities. This study aimed to determine the role of recreational flow experience and well-being on the re-participation intention in recreational sport participants.MethodA personal information form, the “Recreational Flow Experience Scale,” the “Recreational Sport Well-being Scale,” and the “Re-participation Intention Scale” were used as data collection tools. The sample group consisted of a total of 402 voluntary recreational sport participants including 191 women (47.5%) and 211 men (52.5%), who were selected by purposive sampling method in recreational parks and areas in Bingöl, Türkiye. The SPSS software was used to analyze data. Independent Samples t-test, One-Way ANOVA, Pearson Correlation analysis, and Regression analysis methods were used in the analysis process.ResultStatistically significant differences were observed between re-participation intention and the variables of gender, years of participation in sportive recreational activities, and frequency of participation. Statistically significant differences were also found between the frequency of participation in sportive recreational activities and life satisfaction and positive feelings subscales. There was also a statistically significant difference between the years of participation in sportive recreational activities and the recreational flow experience. A moderate positive correlation was found between recreational flow experience, recreational sport well-being, and re-participation intention variables.DiscussionFamily flourishing and positive feelings have a significant relationship on individuals’ intention to re-participate in recreational activities. This suggests that emotional and social well-being may play an important role in the sustainability of participation in recreational sports. As the experience and frequency of participation in recreational sports activities increased, the levels of well-being elevated. Moreover, as the recreational flow experience and recreational well-being level elevated, the intention to re-participate in recreational sport activities increased. For this reason, organizing programs and studies to encourage continuous participation in recreational activities can benefit the well-being level of the society.